Effects of Potassium Levels on Plant Growth, Accumulation and Distribution of Carbon, and Nitrate Metabolism in Apple Dwarf Rootstock Seedlings - Xu, Xinxiang; Du, Xin; Wang, Fen; Sha, Jianchuan; Chen, Qian; Tian, Ge; Zhu, Zhanling; Ge, Shunfeng; Jiang, Yuanmao (Frontiers in Plant Science, 2020)
Nitrogen (N) is one of the most required mineral elements for plant growth, and potassium (K) plays a vital role in nitrogen metabolism, both elements are most widely used for fertilizer in agricultural production. However, the exact relationship between K and nitrogen use efficiency (NUE) remain unclear. Apple dwarf rootstock seedlings (M9T337) were used to study the impacts of different potassium levels on plant growth, nitrogen metabolism, and carbon assimilation in water culture experiments for two years. The results showed that both deficiency and excess in K inhibited the growth and root development of M9T337 seedlings. When the potassium supply concentration was 0 mM and 12 mM, the biomass of each organ, the root-shoot ratio, the root activity and NO3− ion flow rate decreased significantly, net photosynthetic rate (Pn) and photochemical efficiency (Fv/Fm) were lower. Meanwhile, seedlings treated with 6 mM K+ had higher nitrogen and carbon metabolizing enzyme activities and higher nitrate transporter gene expression levels (NRT1.1; NRT2.1). 13C and 15N labeling results showed that deficiency and excess K could not only reduce the 15N absorption and 13C assimilation accumulation of M9T337 seedlings but also reduce the 15N distribution ratio in leaves and the 13C distribution ratio in roots. These results suggest that appropriate K supply level (6 mM) was optimal as it enhanced photosynthetic products transport from the leaves to the roots and increased NUE by mediating photosynthesis, carbon and nitrogen metabolizing enzyme activities, nitrate assimilation gene activities, and nitrate transport.